أسباب التيسير في الفتوى وتطبيقاتها على النوازل المعاصرة = Causes of facilitation in Islamic legal rulings (Fatwas) and its contemporary applications - Abdo Khaled, Nashwan; Al-Nihari, Ameen Ahmad (Universiti Malaya, 2011)
This article found on the causes that call for facilitation in Islamic legal rulings (fatwas) and the application of the theory to practical examples, particularly in contemporary fatwas delivered in response to pressing need and unprecedented contemporary circumstances. The research aims to provide a clear picture of the facility of Syariah, the ease it provides for dealing with unprecedented circumstances and contemporary issues, and it’s capacity for constant renewal and accommodation of new issues that continually crop up in life. In order to achieved the objective, this study tries to apply a descriptive methodology in delineating the concepts of the research and then an analytic methodology in analysing the texts and evidence that provide the basis for facilitation in delivering fatwas. The finding shows the most important being that facilitation is one of the objectives of Syariah and that it varies with variations of circumstance, time and place.